Knowledge and power in Muslim societies : approaches in intellectual history - Morimoto, Kazuo, 1970-; Raz̤avī, Sajjād (Studies in Islamic intellectual history, 2023)
"The study of Islam and of Islamic history is enjoying something of a revival with an emphasis on intellectual history and a greater concern with the ’subaltern’ within that. Why does religion continue to hold significance in our times? Are humans better off, adaptable, less violent, consistently unpredictable? How can we understand the course of our political history and the seeming dominance of democracy and its discontents, not least the legacies of coloniality and empire? While nationalist historiographies prevail in many contexts as well as Marxist and other approaches, the trend seems to be towards connected histories, the transnational and the global. Much of this constitutes intellectual history, which as one leading expert puts it, ”seeks to restore a lost world, to recover perspectives and ideas from the ruins, to pull back the veil, and explain why the ideas resonated in the past and convinced their advocates.“ (Richard Whatmore) Ideas are expressive of cultures and norms, practices and dispositions, of actions and events that lie at the very core of human experience such as sovereignty and power, mind and matter, profanity and spirituality. There are noticeable differences of approach in the various chapters presented but what brings them together is a careful study of texts, not in a reductively philological manner derided quite often these days but in the way in which we recognise that texts are forms of speech acts and lie alongside other forms of self-expression that can elucidate and illuminate as well as occlude"--